Análisis del servicio al cliente en la apertura de cuentas de ahorros en la Cooperativa de Ahorro y Crédito San José Ltda. de la ciudad de Montalvo - Pilco de la Vega, Rodolfo Andres (2021)
The purpose of the study carried out at the “SAN JOSÉ LTDA.” Savings and Credit Cooperative is to determine the process carried out when opening new savings accounts, an activity that is often carried out intensively in this business unit of a financial nature. What has been determined that a high percentage of clients of this cooperative come from the rural area, who on many occasions have to travel more than an hour in vehicles to certain points of the roads and from there must walk to get to their homes. For this reason, they expect personalized attention, but at the same time agile and timely. It has been determined that the opening of savings accounts is under the responsibility of a single person, that at certain times when there is an agglomeration of clients, an agile service is not provided, which annoys users or clients. It is important to note that this business unit has a large clientele, most of which have savings accounts and consumer loans, which are the organization's star product. Modernization using communication technologies through the website does not allow opening savings accounts by electronic means, but rather by presence.